A microfluidic device for practical label-free CD4(+) T cell counting of HIV-infected subjects - Cheng, Xuanhong; Irimia, Daniel; Dixon, Meredith; Sekine, Kazuhiko; Demirci, Utkan; Zamir, Lee; Tompkins, Ronald G; Rodriguez, William; Toner, Mehmet (Lab on a chip, 2007)
Practical HIV diagnostics are urgently needed in resource-limited settings. While HIV infection can be diagnosed using simple, rapid, lateral flow immunoassays, HIV disease staging and treatment monitoring require accurate counting of a particular white blood cell subset, the CD4(+) T lymphocyte. To address the limitations of current expensive, technically demanding and/or time-consuming approaches, we have developed a simple CD4 counting microfluidic device. This device uses cell affinity chromatography operated under differential shear flow to specifically isolate CD4(+) T lymphocytes with high efficiency directly from 10 microliters of unprocessed, unlabeled whole blood. CD4 counts are obtained under an optical microscope in a rapid, simple and label-free fashion. CD4 counts determined in our device matched measurements by conventional flow cytometry among HIV-positive subjects over a wide range of absolute CD4 counts (R(2) = 0.93). This CD4 counting microdevice can be used for simple, rapid and affordable CD4 counting in point-of-care and resource-limited settings.